GEOTURISM IN AFRICA. THE SIMIEN MOUNTAINS - K.A. Novoselov (Минералогия)
The paper is dedicated to the geological structure of Ethiopia and Simien Mountains, which are located in the northern part of the North Ethiopian Plateau composed of Oligocene plateau basalts hosting Oligocene-Miocene shield volcanoes.